Modeling Growth and Yield of Grevillea robusta Grown on Farm Boundary in Nandi County, Kenya - Kiplagat , Cheruiyot Samson; Kinungo , Balozi; Okello , Odwori Paul (African Journal of Education,Science and Technology (AJEST), 2015)
Population pressure has led to changes in land use and livelihood strategies in most highlands of Kenya. This among other factors has contributed to the increased integration of fast growing exotic trees species in to tree-crop production systems on short rotation for socio-economic benefits. Grevillea robusta is one of the exotic species in Kenya which is planted along farm boundaries for fuel wood and timber production. It is normally grown at varied linear spacing and different levels of management. It is preferred by most farmers because of its fast growth and yield as well as its suitability to be integrated with crops. This study investigated growth and yield of Grevillea trees grown in line configuration boundary planting and their economic implication in Nandi County. Farmers growing Grevillea who knew its ages were identified and growth data (height, diameter at breast height-dbh) collected from willing farmers. A total of 985 trees of Grevillea of ages ranging from 1-15 years in 39 different locations within the Upper and lower highland agro-ecological zone in Nandi County were measured. Six independent variables, that is; height, dbh, basal area (BA), age, location and spacing were used in modelling. The results revealed significant differences among the trees for height (P=0.0001), basal area (P=0.0001) and location (P=0.0001). Spacing was not significant (P=0.1993). Height was modeled using the equation Height= -22.1003 + 25.0071 *(Age^0.1566) while dbh was modeled using the equation DBH = -4.4506 + 7.2629 *(Age^0.5971) for growth while volume was modeled using the equation V=D²H. Results of the socio-economic role of boundary planted Grevillea showed that these trees contributed significantly in reducing the gap between supply and demand for wood products in the study area. This study did not find overwhelming evidence (p>0.05) in support of different linear spacing distances thus calling for further research